Problematika Mutu Dan Kompetensi Guru Bahasa Indonesia - Suci Wulan; Missriani Missriani; Siti Rukiyah (STIKes Ibnu Sina Ajibarang, 2023)
The aim of this research is to describe several problems that exist in Indonesia, especially the quality of Indonesian education and teachers and how to overcome them. This research method uses a qualitative descriptive method, this research uses data collection techniques of participant observation, field notes, interviews, documentation studies. These problems are closely related to the qualitay of education and the competence of teachers, especially Indonesian language teachers. nother problem faced by Indonesian language teachers is the lack of training and continuing education. Many Indonesian language teachers do not have adequate training in the latest teaching methods. Relevant continuing education is very important to improve teacher competence.